NARRATIVE FUNCTION IN KAREN M. MCMANUS’S ONE OF US IS LYING - Adam, Navi Maulana; Nurhadi, Muizzu (ELite Journal : International Journal of Education, Language and Literature, 2025)
In literary studies, narratology provides tools to dissect such complex narrative structures. A.J. Greimas’s actantial and functional models offer a systematic approach to analyze the roles of characters and the progression of events within a story. This research discusses about actantial and functional model in Karen M. Mcmanus’s One of Us is Lying. This research aims to explain and describe the role of actant and functional model by Greimas’ narrative in shaping the mystery novel. The theory and approach used as a guide to analyse and describe how the structure of mystery fiction portrayed in this novel. Descriptive qualitative is used in this research. The findings of this research show that is total one main actant and functional scheme. The results of this research show that functional model depict dynamic character interactions and plot progression, driven by factors of shifts in time and place, new events, character arguments, character’s arrivals, and conflicts that significantly develop the plot and heighten the tension of the mystery fiction. Among the six actants, the helper actant is plays important role, assisting the subject actant in obtaining their goals through necessary clues and information. Without the helper, the subject would struggle to solve the mystery.